Exploring primary school teachers' language of thinking: a case study = Bahasa berfikir guru sekolah rendah: satu kajian kes - Wan Yusoff, Wan Mazwati; Che Seman, Shamilati; Embong, Rahimah (IIUM Press, International Islamic University Malaysia, 2017)
The aspiration of Malaysian education system as mentioned in the Malaysia Education Blueprint 2013-2025 is to produce students who are highly critical and creative. Since teaching for higher order thinking was made explicit since 1989, a systematic evaluation of the adequacy and pitfalls of teaching for thinking programs was not done extensively. If examination result is the yard stick to measure the impact of teaching for thinking, then it can be concluded that 2016 UPSR result painted a dismal picture of failure in teaching for thinking. Studies showed that there is a positive correlation between language teacher used to communicate in the classroom and the development of thinking dispositions among students. Using the framework of language of thinking put forward by Costa and Marzano (2001), this study was conducted to explore language of thinking used by teachers during teaching and learning sessions in several primary school classrooms. This preliminary study attempted to gain in-depth understanding of the phenomenon in the actual setting so that the insight can illustrate a wider picture of the issue. This exploratory case study employed structured observations to collect data in the classroom of nine primary school teachers. The data was analysed based on theoretical proposition by Costa and Marzano. Findings revealed that teachers needed to improve their language of thinking.